Intervention of Combination of Swedish Massage Therapy with Lavender Aromatherapy in Reducing Stress and Blood Pressure in Hypertensive Patients - Billy Anoraga, Aditya; Suhita, Byba Melda; Kusumawati, Prima Dewi; Indasah; Ambarika, Rahmania; Prasetyo, Joko (Chakra Brahmanda Lentera Institute, 2024)
Background: Severe stress is one of the causes of hypertension, both the elderly, young adults and middle-aged people. Stress and increased blood pressure experienced by a person are the causative factors for hypertension. The purpose of this study is to analyze the effect of the combination of Swedish Massage Therapy with Lavender Aromatherapy on stress and blood pressure in hypertensive patients. Methods: This study is a quantitative research that uses a quasy experiment research design with a pretest - posttest control group design approach. The population of all hypertension patients in the Working Area of the Karangan Health Center, Trenggalek Regency is 107 people. The sample size was 54 respondents. The sampling technique is purposive sampling. The independent variables of the study were the Combination of Swedish Massage Therapy with Lavender Aromatherapy and the dependent variables were stress and blood pressure. The analysis used the Mann Whitney test with a significant p value < 0.05. Result. Results: of the study using the Mann Whitney test showed a p value of 0.000 or < 0.05 related to stress and blood pressure between the intervention group and the control group after the combination of Swedish Massage Therapy and Lavender Aromatherapy. Conclusion: The combination of Swedish Massage Therapy with Lavender Aromatherapy is effective in reducing stress and blood pressure in hypertensive patients. This intervention is very easy to do, so it can be applied as a nursing intervention in the work area of the health center for the development of nursing science.